PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN SEKTOR EKONOMI KREATIF (Studi Kasus Pada Perusahaan Arsitektur Subsektor Kontruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Nur Kholis Masruhin; Jeni Susyanti; M Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to determine the effect of financial performance which includes liquidity ratios, leverage, coverage, and profitability on the value of the firm's creative economy sector of the building construction subsector found on the Indonesia Stock Exchange for the period 2015-2017. The population used in this study are all building construction architecture companies found on the Indonesia Stock Exchange. The sample selection uses the purposive sampling method, based on the criteria obtained by 12 companies. The method used is multiple linear regression analysis with testing hypothesis using the t test and test f.The results of this study indicate that partially liquidity ratios, leverage ratios, and profitability ratios have a significant positive effect on firm value while the coverage ratio does not have a partial effect on firm value. Simulatan liquidity ratio, leverage, coverage, and profitability have a significant influence on firm value.Keywords: Creative Economy, Financial Performance and Corporate Value